HUMANITY VALUES IN THE VIDEO ZAIN RAMAḌĀN 2019 AL-DIN TAMAM AL-AKHLAQ: ROLAND BARTHES' SEMIOTICS STUDY - Habibah, Siti Ummi; Mazaya, Nur Widad (Afshaha: Jurnal Bahasa dan Sastra Arab, 2023)
Religious tolerance is an essential requirement for a harmonious and peaceful religious life in society. Therefore, supporting religious tolerance can help societies achieve greater diversity and harmony, and reduce conflicts and misunderstandings that may arise due to differences in religious beliefs. Support for religious tolerance at this time can be shown in various ways, one of which is through videos entitled Zain Ramaḍān 2019 Al-Din Tamam Al-Akhlaq. This study aims to elaborate on the human values contained in the video Zain Ramaḍān 2019 Al-Din Tamam Al-Akhlaq. To find out these messages and values, the theory used to analyze the video is Roland Barthes' semiotics, namely the meaning of signs at the first level in the form of denotative meanings and the meaning of signs at the second level in the form of connotative and mythical meanings. This research is included in descriptive qualitative research. The data in this study were obtained through the listening method and note-taking technique then analyzed by the semiotic study of Roland Barthes. The results showed that there were semiotic signs, both verbal and nonverbal signs in the video which contained denotative, connotative and mythical meanings. Through these two processes of reading the Barthes sign, it can be seen that the values contained in the videoZain Ramaḍān 2019 Al-Din Tamam Al-Akhlaq include maintaining unity and harmony, messages of peace between religious communities, making friends without barriers, loving children, and freedom of speech. These values represent the role of religion as a complement to human morality